2020
DOI: 10.9734/ajeba/2019/v13i430179
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Investigation of Effective Management of Working Capital on Firm Performance: Evidence from the Nigerian Agricultural Sector

Abstract: The focus of this study is to find out the link between working capital management and firm performance in agriculture firms listed in the Nigerian stock exchange. The research used yearly data for Livestock Feeds Plc from 2002 to 2018 and Okomo oil company Plc from 2007 to 2018. The study employed cash conversion cycle, account payables, account receivables and inventory turnover as stimulus variables with earnings per share as outcome variable. The data was analyzed employing descriptive statistics, ADF unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…( 2018) recommended in their study on effects of investment decisions on listed firms at Nairobi Securities Exchange that since investment decisions affect performance positively and significantly there is need for listed firms to focus more investing in firm machinery, property, plants and equipment so as to boost their investment returns. Peter and Nelson(2020),in their study on effect of financial management practices on firm performance in Nigeria revealed that, earnings per share and working capital management signified by account receivables is found to have positive and statistically significant effect. The relation between earnings per share and account payables is established to be negative and statistically insignificant for the Nigerian companies under study.…”
Section: Empirical Studiesmentioning
confidence: 95%
“…( 2018) recommended in their study on effects of investment decisions on listed firms at Nairobi Securities Exchange that since investment decisions affect performance positively and significantly there is need for listed firms to focus more investing in firm machinery, property, plants and equipment so as to boost their investment returns. Peter and Nelson(2020),in their study on effect of financial management practices on firm performance in Nigeria revealed that, earnings per share and working capital management signified by account receivables is found to have positive and statistically significant effect. The relation between earnings per share and account payables is established to be negative and statistically insignificant for the Nigerian companies under study.…”
Section: Empirical Studiesmentioning
confidence: 95%
“…On the other hand, there are a cup full of local researches that have tilted towards the direction of the present study. Such studies conducted in Nigeria include; Olaoye, Adekanbi & Oluwadare (2019) and Peter & Nelson (2019) concluded that a positive relationship existed between working capital management and firm performance. In contrast, Osuma, Ailemen, Osabohien & Eriki (2017) reported a negative relationship and Oladimeji & Aladejebi (2020) reported that there was no relationship between working capital management and SMEs' profitability in Nigeria.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Usually, financial managers have to make a crucial financial decision to determine the company's value. However, firm performance measures companies' earnings, profits, and appreciation in share value arising from efficient and effective positioning of the organization's resources (Peter & Nelson, 2020) [43] . Firm performance is one of the driving forces of growth and development of any economic activities in the world.…”
Section: Introductionmentioning
confidence: 99%